Transfer of maternal cholesterol to embryo and fetus in pregnant mice - Shumi Yoshida; Yoshinao Wada (Journal of Lipid Research, 2005)
Cholesterol is essential for antenatal development. However, the transport of maternal cholesterol to the embryo has not been sufficiently studied, and that to the fetus is still controversial. To this end, a 1 mg dose of [3,4-13C2]cholesterol was injected daily into pregnant mice and the labeled cholesterol was measured by gas chromatography-mass spectrometry. After venous injections from days 10 to 17 of gestation, [13C]cholesterol levels in total (12C and 13C) cholesterol were increased to 5.1% and 2.8% in maternal and fetal plasma, respectively. Labeled cholesterol was identified in the liver, kidneys, and intestines, but not in the brain, of the fetus. After injections from days 1 to 8, [13C]cholesterol levels were increased to 12.4% and 8.0% of total cholesterol in maternal plasma and the embryo, respectively. The level of 11.5% in the yolk sac was higher than that in the embryo.Intrauterine transfer of maternal cholesterol to the embryo as well as the fetus was evident in mice, and both the placenta and the yolk sac appear to be sites of intermediate passage in murine pregnancy.